Performance of MIMO systems with a hybrid of transmit diversity and spatial multiplexing - Almeida, André Lima Férrer de (2003)
Spatial multiplexing or BLAST (Bell Labs Layered Space-Time) and space-time block-coding (STBC) are promise approaches that exploits the MIMO channel to provide higher data rates and diversity gains with no sacrifice in bandwidth. In this work we evaluate the performance of a MIMO system that combines transmit diversity and spatial multiplexing schemes. We also propose two effective receiver structures for this hybrid transmission scheme. Our simulation results show that the performance of the hybrid scheme along with the proposed receivers is excellent, outperforming pure BLAST-based systems and with higher data rates than a pure STBC system.